First Principles Investigation of the Effect of Vanadium Doping on Electronic Structure, Magnetic, and Optical Properties of Graphene–Boron Nitride Heterostructure - Berhanu Aymalo Shalisho; Markos Meskele Shanko; Sintayehu Mekonnen Hailemariam (Advances in Condensed Matter Physics)
We investigate the effect of vanadium (V) doping on the electronic, magnetic, and optical properties of the graphene/hexagonal boron nitride (G/h-BN) heterostructure using spin-polarized density functional theory (DFT). Defect formation energy calculations show that the V atom prefers substituting boron (B) sites over nitrogen (N) sites and the V-doped G/h-BN heterostructures are energetically stable. The lattice constant of the V-doped G/h-BN increases due to the larger atomic radius of the V atom. The electronic band structure analysis reveals that the band gap of G/h-BN increases from 0.053 to 1.25 eV with 2.08% V doping. The total density of states (TDOSs) analysis indicates a transition from paramagnetic to ferromagnetic (FM) behavior upon V doping. Moreover, the magnetic energy (∆E) calculations show that two V dopants in G/h-BN favor FM interactions, although the energy decreases as the distance between dopants increases. Using mean-field theory combined with spin-polarized DFT, we estimate the corrected FM transition temperature (Tc) to be 457 K for 4.16% V doping in G/h-BN. Additionally, optical absorption analysis shows a significant enhancement in the absorption coefficient in the visible region due to V doping. This study offers insights into the potential use of V-doped G/h-BN for spintronic and optoelectronic applications, subject to further theoretical and experimental validation.